Membrane Vesicles Derived From Clostridium botulinum and Related Clostridial Species Induce Innate Immune Responses via MyD88/TRIF Signaling in vitro - Kobayashi, Nobuhide; Abe, Kimihiro; Akagi, Sachiyo; Kitamura, Mayu; Shiraishi, Yoshitake; Yamaguchi, Aki; Yutani, Masahiro; Amatsu, Sho; Matsumura, Takuhiro; Nomura, Nobuhiko; Ozaki, Noriyuki; Obana, Nozomu; et al. (Frontiers in Microbiology, 2022)
Clostridium botulinum produces botulinum neurotoxin complexes that cause botulism. Previous studies elucidated the molecular pathogenesis of botulinum neurotoxin complexes; however, it currently remains unclear whether other components of the bacterium affect host cells. Recent studies provided insights into the role of bacterial membrane vesicles (MVs) produced by some bacterial species in host immunity and pathology. We herein examined and compared the cellular effects of MVs isolated from 4 strains of C. botulinum with those of closely related C. sporogenes, and 2 strains of the symbiont C. scindens. MVs derived from all strains induced inflammatory cytokine expression in intestinal epithelial and macrophage cell lines. Cytokine expression was dependent on Toll-like receptor (TLR) 2/4 and nucleotide-binding oligomerization domain (NOD) 1/2, pattern-recognition receptors for cell wall components. MVs were phagocytosed by RAW264.7 cells, and the inhibition of phagocytosis did not reduce the induction of cytokine expression. On the other hand, the inhibition of dynamin or phosphatidylinositol-3 kinase (PI3K) suppressed the induction of cytokine expression by MVs, suggesting the importance of these factors downstream of TLR signaling. The present results indicate that MVs from C. botulinum and related clostridial species induce host inflammatory responses.